A Collaboration Between Communicative Language Teaching (CLT), Audiolingual, and Community Language Learning (CLL) Approach in Teaching and Learning English at SMA 1 Singorojo Kendal - Haryani Haryani; Ainur Putry (Journal of English Education and Teaching, 2020)
This research aimed to investigate and analyze the collaboration of communicative language teaching approach, audiolingual method, and cooperative language learning method which were applied during teaching - learning process in twelve grade of science 2 students in SMA 1 Singorojo Kendal.  This research employed descriptive qualitative research design. The instruments of this study were interview and observation which took approximately fifty minutes. In order to motivate and improve students’ speaking ability, so the teacher taught them in simple way first, then followed by synthesizing both of essentials methods and techniques. The result showed that teacher designed the classroom activity by implementing curriculum 2013 in which emphasized on communicative language teaching (CLT) approach. The researchers found that the teacher organized some methods in delivering material. He also provided fun and interesting games to encourage students’ motivation in learning English.The researchers infer that there are collaboration between CLT approach, audiolingual method, and CLL method as an alternative strategy in learning English.